Habitat Characterisation for the Macro Moth Fauna (Lepidoptera: Heterocera) of the Cachar District of Southern Assam, India - Choudhury, Maniza; Islam , Mofidul; Choudhury , Parthankar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study conducted in the Cachar district involved a comprehensive characterisation of the local flora, identifying a total of 146 tree species from 50 families. The average species richness among tree species in moth habitats was estimated to be S=47.94±9.84. Dominant tree species found across all study sites in the Cachar district included Lagerstroemia reginae Roxb., Michelia champaca L., Tectona grandis L.f., Bombax ceiba L., Dalbergia sisoo Roxb., and others. Additionally, 74 shrub species from 28 families were identified across the study area, with an average species richness in moth habitats of S=23.31±5.34. Shrub species with higher density reported in this study included Melastoma malabathricum L., Triumfetta rhomboides Roxb., and others. Furthermore, the survey identified 87 herb species from 41 families across the study sites in the Cachar district. The average species richness of herb species in moth habitats was determined to be S=58.57±32.99. Herb species with higher density documented in Cachar district during the study included Polygonum microcephala (D. Don.) Sasaki, Cynodon dactylon (L.) Pers., and others. The study also highlighted food or host plants preferred by the Arctiidae, Geometridae, and Sphingidae moth families, belonging to various families such as Solanaceae, Moraceae, Poaceae, and others. This research significantly contributes to our understanding of the rich biodiversity of the Cachar district and the essential role played by plant species in supporting moth habitat.